2005
DOI: 10.2106/jbjs.d.02813
|View full text |Cite
|
Sign up to set email alerts
|

The Reverse Shoulder Prosthesis for Glenohumeral Arthritis Associated with Severe Rotator Cuff Deficiency<sbt aid="1022701">A Minimum Two-Year Follow-up Study of Sixty Patients</sbt>

Abstract: The data from this study suggest that arthroplasty with the Reverse Shoulder Prosthesis may be a viable treatment for patients with glenohumeral arthritis and a massive rotator cuff tear. However, future studies will be necessary to determine the longevity of the implant and whether it will provide continued improvement in function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
312
1
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 491 publications
(346 citation statements)
references
References 28 publications
17
312
1
10
Order By: Relevance
“…Of the 45 patients of this review for whom the subjective outcome of surgery was reported [42,44,46], 77 % considered their results as excellent or good. This rate is comparable to that obtained recorded in several studies in which the RSA was mostly implanted for massive cuff tears or CTA [10,13,31,51].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Of the 45 patients of this review for whom the subjective outcome of surgery was reported [42,44,46], 77 % considered their results as excellent or good. This rate is comparable to that obtained recorded in several studies in which the RSA was mostly implanted for massive cuff tears or CTA [10,13,31,51].…”
Section: Discussionsupporting
confidence: 87%
“…The mean prevalence of scapular notching was 35 %, which is similar to the percentages reported in several studies [13,31,33,34] in which the rate ranged from 43 to 51 %, and lower than the 68 % found by Boileau et al [9]. As in other studies [30,33], the notching did not appear to affect the clinical outcome.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, a recent study has shown that this technique alone is not sufficient to avoid notching [13]. Frankle [18] has conceived a model of reverse prosthesis with an increased lateral offset of the glenosphere and/or baseplate. However, the lateralisation of the glenoid component that is achieved has the drawback of increasing the torque or shear force on the glenoid, and thus could potentially increase the risk of loosening of the component.…”
Section: Discussionmentioning
confidence: 99%